LEACH-J: UMA PROPOSTA DE ALGORITMO DE CLUSTERIZAÇÃO MAIS JUSTO PARA O PROTOCOLO LEACH - Carvalho, Carlos Eduardo da Silva (2010)
Wireless sensor networks (WSN) are considered as a special type of wireless network (ad hoc) and present challenges such as limited energy, bandwidth restrictions and use of communication channels with high level of noise. The restriction of energy is one of the most important factors in WSN project because it demands specific requirements in the construction of sensor nodes and in all layers of the protocol stack, particularly in the routing protocols. The several routing protocols that have been proposed for WSNs can be classified into flat routing protocols (when all sensor nodes perform the same task) and hierarchical routing (when the sensor nodes are organized in groups clusters leaving the leader of each group cluster-head with the task of transmitting data to the base station). In this work is proposed a new algorithm based on the hierarchical routing protocol LEACH (Low-Energy Adaptive Clustering Hierarchy) that is one of the main references on clustering in WSN. The proposed protocol LEACH-J differs from LEACH and other of its variants by the clustering algorithm, incorporating a new way of choosing cluster-heads and forming clusters. The performance of LEACH-J is compared with the original LEACH protocol and its variant LEACH-C through simulations. The results obtained show that LEACH-J may improve the performance related to these traditional approaches for clustering in WSN.